Hints on the Study of Persian - Kanga, Pestonjee Kavasjee, (Brill | Manohar Publishers & Distributors, 2024)
This slim volume is the study of Persian grammar for the intermediate level. It is a step-by-step methodology of studying Persian grammar and also serves as a teach-yourself book. It is highly recommended for students, linguists, and enthusiasts interested in Persian culture and language, and is useful for translation and advanced studies in Persian language and literature.